Link Adaptation for Microwave Link using both MATLAB and Path-Loss Tool - Jide Julius Popoola; Damiane Okhueleigbe; Isiaka Alimi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2016)
The inherent multipath transmission on wireless channels usually leads to signal fading which eventually degrades the system performance. In mitigating this problem, link adaptation has been identified as a promising scheme that helps in maximizing the system spectral efficiency (SE) in dispersive wireless channels. In this paper, link adaptation based on adaptive modulation and coding was used to study the performance of M-ary quadrature amplitude modulation radio system subjected to multipath fading. MATLAB® scripts and Simulink model were developed to compare the effect of wireless channel on different constellation sizes. Also, transmission link on Federal University of Technology Akure campus’ path terrain was designed with the aid of path-loss® tool application software in order to further analysis the effect of using different modulation formats on the system performance. The results show that, employment of link adaptation scheme offers better performance regarding the system availability and SE